2021
DOI: 10.15540/nr.8.1.57
|View full text |Cite
|
Sign up to set email alerts
|

The Road Less Traveled: Integrating Neurotherapy with Holistic Neuropsychological Rehabilitation After Severe Head Injury

Abstract: Introduction: Traumatic brain injury (TBI) is associated with physical, cognitive, emotional, and behavioral disturbances. The cognitive deficits are common after TBI, and a holistic approach to neuropsychological rehabilitation is recommended in these patients. EEG neurofeedback training (EEG-NFT) is a state-of-the-art technique for neuropsychological rehabilitation. There is a paucity of studies exploring the use of EEG-NFT integrated with holistic neuropsychological rehabilitation. Method: Single case desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The results of this study demonstrated the beneficial and stable long-term effects of holistic neuropsychological rehabilitation but also highlighted some areas that require further consideration (Shany-Ur et al 2020 ). Similar studies have found positive effects of holistic rehabilitation on psychological, emotional, and quality of life measures, although the benefits on cognitive functions have been mixed (Afsar et al 2021 ; Exner et al 2021 ; Holleman et al 2018 ; Nilsson et al 2011 ; Sarajuuri et al 2018 ; Urech et al 2020 ).…”
Section: Holistic Approachmentioning
confidence: 85%
See 2 more Smart Citations
“…The results of this study demonstrated the beneficial and stable long-term effects of holistic neuropsychological rehabilitation but also highlighted some areas that require further consideration (Shany-Ur et al 2020 ). Similar studies have found positive effects of holistic rehabilitation on psychological, emotional, and quality of life measures, although the benefits on cognitive functions have been mixed (Afsar et al 2021 ; Exner et al 2021 ; Holleman et al 2018 ; Nilsson et al 2011 ; Sarajuuri et al 2018 ; Urech et al 2020 ).…”
Section: Holistic Approachmentioning
confidence: 85%
“…In addition to cognitive impairments following ABI, deficits in metacognition and emotional disturbances including depression and anxiety can be present and impact daily functioning and community participation such as returning to work (Afsar et al 2021;Haskins et al 2012;Long et al 2014;Perna and Harik 2020;Robertson and Schmitter-Edgecombe 2015). Metacognition refers to the knowledge of one's own cognitive abilities and includes self-awareness, self-monitoring, and self-regulation (Al Banna et al 2015;Robertson and Schmitter-Edgecombe 2015;Sansonetti et al 2021).…”
Section: Factors That Influence Memory Rehabilitation Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In rehabilitation, SCEDs have been used in a variety of areas. The main focus includes the evaluation of cognitive and behavioral interventions for aphasia, 8 neuropsychological rehabilitation, 9 and special education. 10 In recent years, SCEDs have been more widely applied to areas such as sport training, 11 and the effectiveness of animal-assisted therapy, 12 among others.…”
mentioning
confidence: 99%